The effect of the time parents spend with children on children's well-being - Li, Dongxu; Guo, Xi (Frontiers in Psychology, 2023)
Background: The time with parents is a crucial factor in the growth of children, and children’s well-being is an important indicator of their mental health. Methods: To promote the improvement of children’s well-being, relying on data from the 2017 China Time Use Survey (CTUS), this study explores the relationship between parental time and children’s well-being and specific influencing factors. Results: The more time parents spent with children, the higher their children’s well-being (coefficient 0.1020, p<0.01). The life and leisure time parents spent with children promotes children’s well-being (coefficient 0.1020, p<0.01). The life and leisure time mother spent with children (coefficient 0.1030, p<0.05), and the life and leisure time (coefficient 0.1790, p<0.05) and educational interactions time father spent with children (coefficient 0.3630, p<0.10) positively affect children’s well-being. The influence of the time parents spent with children on children’s well-being is heterogeneous based on children’s academic performance. Conclusions: The accompanying of parents is an important determinant of children’s well-being. Family education, guidance services and mental health services should be strengthened, and it is necessary to improve the time spent with children and pay attention to individual differences in children.